2019
DOI: 10.1093/pm/pnz260
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Patient-Specific Opioid Prescribing and Tapering Protocol Is Associated with a Decrease in Total Opioid Dose Prescribed for Six Weeks After Total Hip Arthroplasty

Abstract: Abstract Objective This retrospective cohort study tested the hypothesis that implementing a multidisciplinary patient-specific discharge protocol for prescribing and tapering opioids after total hip arthroplasty (THA) will decrease the morphine milligram equivalent (MME) dose of opioids prescribed. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Interestingly, Howard et al (2018) found that after implementing evidence-based opioid prescribing recommendations for a single surgical procedure (laparoscopic cholecystectomy), discharge opioid prescriptions decreased for four other unrelated surgical procedures without significantly affecting refill rates, described as the “spillover effect” [ 37 ]. In addition to procedure-specific protocols, recent studies suggest that patient-specific prescribing and tapering protocols based on a review of the patient’s personal opioid consumption prior to discharge leads to decreased persistent opioid use after discharge [ 38 , 39 ]. Other simple yet effective interventions include lowering discharge opioid prescription defaults in the electronic health system [ 40 ] and the creation of evidence-based procedure-specific discharge ordering sets [ 41 ].…”
Section: Postoperative Interventionsmentioning
confidence: 99%
“…Interestingly, Howard et al (2018) found that after implementing evidence-based opioid prescribing recommendations for a single surgical procedure (laparoscopic cholecystectomy), discharge opioid prescriptions decreased for four other unrelated surgical procedures without significantly affecting refill rates, described as the “spillover effect” [ 37 ]. In addition to procedure-specific protocols, recent studies suggest that patient-specific prescribing and tapering protocols based on a review of the patient’s personal opioid consumption prior to discharge leads to decreased persistent opioid use after discharge [ 38 , 39 ]. Other simple yet effective interventions include lowering discharge opioid prescription defaults in the electronic health system [ 40 ] and the creation of evidence-based procedure-specific discharge ordering sets [ 41 ].…”
Section: Postoperative Interventionsmentioning
confidence: 99%
“…The key characteristics of the 66 included studies [ 5 , 50 114 ] are detailed in Table 1 : Study Characteristics, Description of Strategies and Outcomes. Most studies used a retrospective cohort ( n = 35) [ 5 , 52 , 56 , 60 , 72 74 , 78 89 , 91 – 94 , 97 – 99 , 101 105 , 108 , 109 , 111 , 112 ], a randomized controlled trial (RCT) ( n = 24) [ 50 , 51 , 53 55 , 57 , 59 , 61 , 62 , 65 71 , 75 , 76 , 95 , 100 , 106 , 107 , 113 , 114 ] or a prospective cohort ( n = 7) [ 58 , 63 , 64 , 77 , 90 , 96 , 110 ] design. Almost all the studies were conducted in the U.S. ( n = 58) [ 5 , 50 57 , 59 – 61 , 63 , 67 74 , 77 99 , 101 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors for chronic opioid use (e.g., previous opioid use, benzodiazepine use, substance abuse, mental health disorder, chronic pain) were measured in close to 70% of studies [ 5 , 50 , 51 , 56 58 , 61 , 63 , 64 , 67 , 68 , 72 74 , 78 , 79 , 82 89 , 92 95 , 97 – 100 , 102 114 ] (Supplemental Digital File 4 : Risk factors for chronic opioid use in included studies by types of strategies). The main risk factors involved were depression/anxiety or associated medication use [ 51 , 53 , 56 , 57 , 63 , 64 , 72 74 , 78 , 79 , 82 , 83 , 85 89 , 92 , 97 , 100 , 102 , 104 , 107 , 109 , 112 , 114 ], and prior opioid use [ 5 , 53 , 57 , 58 , 61 , 63 , 64 , 67 , 68 , 73 , 74 , 78 , 82 , 83 , 85 89 , 95 , 97 –…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent article describing a multidisciplinary patient-specific opioid prescribing and tapering protocol after lower extremity arthroplasty suggests a reasonable goal of return to baseline opioid use after recovery from surgery. 28 In conclusion, there has been tremendous progress in the field of acute perioperative pain medicine. Effective pain management to facilitate early mobility is a critical element of modern ERPs for surgical patients.…”
Section: After Surgerymentioning
confidence: 99%